Soil texture and porosity of the PhytOakmeter plot DKr (Kreinitz, Germany) in 2020 - Max Köhne; Martina Stange; Sylvie Herrmann; Marie-Lara Bouffaud (PANGAEA, 2025)
As part of PhytOakmeter platform (www.phytoakmeter.de), soil porosity and soil texture were measured in 2020. Soil cores were taken at three depths (15cm, 30cm and 45cm) with six replicates at each depth. The dataset contains the values of soil density (g/cm3), soil porosity (cm3/ cm3), soil organic content (%), coarse silt (%), medium silt (%), fine silt (%), clay (%), coarse sand (%), medium sand (%), fine sand (%), total mineral content (%) and soil texture. Soil texture was classified according to Bodenkundliche Kartieranleitung (KA5, 2005; ISBN 978-3-510-95920-4) and grain size analysis with the KÖHN analysis according to DIN ISO 11277.
In: Herrmann, Sylvie; Bouffaud, Marie-Lara (2025): Soil texture, soil physicochemical properties and climatic data from the PhytOakmeter plot DKr (Kreinitz, Germany) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.982540